Food Self-Sufficiency and the Challenges of Family Resilience in Indonesia: Bridging Adaptive Policies - Muhammad Sawir; Susilawaty Susilawaty (Journal of Governance, 2026)
This study aims to analyze the impact of the food self-sufficiency policy on family resilience, identify existing barriers, and formulate adaptive strategies to sustainably strengthen family resilience. This study used qualitative methods and was analyzed using NVivo 12 Plus. The study's findings indicate that although the food self-sufficiency policy in Indonesia has successfully maintained rice availability and reduced food insecurity in some regions, its impact on family resilience remains limited. Inequality in nutritional consumption, the high prevalence of stunting, and the large proportion of household expenditure on food indicate that focusing on production quantity is insufficient to address the issues of nutritional quality, affordability, and equitable access to food. Barriers such as dependence on rice, limited logistical infrastructure, the socio-economic conditions of smallholder farmers, and weak price stabilization exacerbate these conditions. Therefore, adaptive policies based on food diversification, farmer protection, nutrition education, and strengthened distribution.